Mobilisations environnementales et dynamiques des territoires : le cas de Plaine Commune, communauté d’agglomération d’Ile-de-France - Nathalie Blanc; Alice Canabate; Nicolas Douay; Angela Escobar; Flaminia Paddeu (VertigO)
In continuation with the work on civic environmentalism, which focus on how local activism reconfigures citizen engagement in urban space and governance, in the perspective of the ecological transition, the authors of this article examine the role of urban agriculture associations in the Plaine Commune institutional territory (communauté d’agglomération) of Ile-de-France. It appears as a double territorial logic related to both the nature of the actors and to the spatial and socio-political dynamics.